Mechanization of milk production in the rotary milking parlor with loose cubicle technology for cow keeping - Kudrin M.R. (BIO Web of Conferences, 2021)
The research was carried out in “Udmurtia” agricultural produc-tion co-operative (collective farm) of the Vavozhsky district of the Udmurt Republic". A complex for keeping 1200 cows with loose cubicle technolo-gy for cow keeping with milking in the milking parlor using the rotary milking equipment was built on the farm for the first time in the Udmurt Republic. In the course of the study, technological operations during keep-ing, feeding, milking cows at the rotary milking unit were studied; the tim-ing of the cow milking process and the sequence of operations were carried out. Based on the research results, specific recommendations were given to the farm.